Respostas

2013-06-04T17:14:26-03:00

Dados:
A = x² + y³
B = x4 + 2x²y³
C = x4 + y³

Determinar: 
a) A² - B
(x² + y³)² - (x4 + 2x²y³) = (x² + y³) (x² + y³) - (x4 + 2x²y³) = x4 + 2x²y³ + y6 - x4 -2x²y³ = y6

Resposta: A² - B = y6 (Y elevado a 6)

b) A + B - C
(x² + y³) + (x4 + 2x²y³) - (x4 + y³) = x² + y³ + x4 + 2x²y³ - x4 - y³ = x² + 2x²y³ 

Resposta: A + B - C = x² + 2x²y³ (ou: x²(1 + 2y³)

c) A x C
(x² + y³) (x4 + y³) = x6 + x²y³ + y³x4 + y6 = x6 + x²y³ + x4y³ + y6 (ou: x6 + x²y³(1 + x²) + y6)


Resposta: A x C = x6 + x²y³(1 + x²) + y6

 

acho que e isso!

1 5 1